Tetrazine metallation boosts rate and regioselectivity of inverse electron demand Diels-Alder (iEDDA) addition of dienophiles - Schnierle, Marc; Blickle, Svenja; Filippou, Vasileios; Ringenberg, Mark R (Chemical communications (Cambridge, England), 2020)
Reported herein is the coordination of rhenium complexes to tetrazine ligand in [ReCl(CO)3(TzPy)] [1] (TzPy = 3-(2-pyridyl)-1,2,4,5-tetrazine) and the rates of addition of different dienophiles to the tetrazine. Tetrazine coordiation lowers the ΔS‡ contribution to ΔG‡ for iEDDA addition.Reported herein is the coordination of rhenium complexes to tetrazine ligand in [ReCl(CO)3(TzPy)] [1] (TzPy = 3-(2-pyridyl)-1,2,4,5-tetrazine) and the rates of addition of different dienophiles to the tetrazine. Tetrazine coordiation lowers the ΔS‡ contribution to ΔG‡ for iEDDA addition.